A study on physicians' adherence to joint national committee guidelines for hypertension - Nagavaishnavi Venkata Bhaskara; Ravi Kiran Andra; Medha Bhat; K K Mithun Reddy; Ravi Shankar; Amogh Diwakar; Pratibha D Nadig (Wolters Kluwer Medknow Publications, 2022)
Background: Increased blood pressure (BP) is the second leading risk factor for death and disability globally according to the Global Burden of Disease Study. Therefore, various guidelines have been issued. The American College of Cardiology/American Heart Association issued guidelines and Joint National Committee (JNC) 7 and JNC 8 guidelines, which were laid down by the JNC are a few guidelines for hypertension (HTN) management. Many countries have not implemented effective public policies to prevent and control HTN. Objective: The objective of this study was to assess the number of physicians' adherent to JNC 7, JNC 8, and AHA guidelines when prescribing medications to patients. In addition, the efficacy of the medications, trends in prescribing medications, and adverse drug reactions that a few patients presented with were assessed. Materials and Methods: A cross-sectional, questionnaire-based observational study was conducted on hospitalized hypertensive patients in a tertiary care hospital in South India. Data were collected on a detailed interview basis after receiving an informed consent based on a specific set of preformulated questions. The sample size was met, and the obtained data were analyzed appropriately using the SPSS software version 21. Results: Seventy two patients had diabetes and/or CKD along with hypertension out of 198 patients who participated in the study.Maximum number of prescriptions were adherant to JNC 8 and the least were observed with AHA guidelines.The blood pressure was more controlled in those patients where physicians were adherant to guidelines.The most commonly prescribed drugs were Calcium channel blockers followed by Angiotensin receptor blockers,beta blockers and ACEinhibitors. Adverse drug reactions were seen in only 5 patients Conclusion: The overall adherence to antihypertensive medications guidelines by physicians in India is only modest and much lesser when comorbidities are associated. There is a need to build awareness. Further the antihypertensive classes of medications currently recommended appear to be efficacious and safe.